Kepedulian Mahasiswa UPI Terhadap Perkembangan Pemilu Indonesia Tahun 2024 - Eva Rachel Meisyana Sianipar; Anggy Septriyani; Tiara Dwi Putri NSP; Maulia Depriya Kembara (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This paper aims to reveal the paradigm in fostering public awareness in democracy, the extent and form of plurality and democracy of Indonesian society in the future. Discusses the concept of the Sila Kerakyatan as the basis for the Indonesian political system led by wisdom in deliberation and representation, and its implications for the level of voter participation in the electoral process. The method used is descriptive analysis with a qualitative approach that provides an overview of problem solving based on critical analysis and the author's interpretation, based on literature that the author gets from various sources and references. The findings obtained Growing public awareness in instilling democratic values, can be done by (a) Opening a democratic class this program aims to introduce, foster habituation to democracy. Education of democratic awareness from an early age can and must continue to be carried out by various groups, the essence of democracy at the individual level is internalized, so efforts to uphold democracy in structural and cultural currents can be realized. (b) Organizing character education, building a democratic society is a necessity that must be carried out by a country that adheres to a democratic system. Democracy is not understood as a way of managing government but as democratization.